2020
DOI: 10.1124/dmd.120.000010
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 Antioxidative System is Involved in Cytochrome P450 Gene Expression and Activity: A Delay in Pentobarbital Metabolism in Nrf2-Deficient Mice

Abstract: NF-E2-related factor 2 (Nrf2) is a transcriptional regulator of biologic defense proteins, such as antioxidant proteins and phase II detoxification enzymes. Cytochrome P450 (P450) enzymes have been shown to regulate phase I metabolism of various drugs and are partially regulated by Nrf2; however, the influence of Nrf2 on drug pharmacokinetics is not known. Here, we showed that Nrf2 depletion prolonged the effect of pentobarbital, a sleep-promoting drug. Pretreatment with phenobarbital, a P450 inducer, shortens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…CYP1A2 was enriched in reactive oxygen species metabolic pathways. It has been reported that CYP1A2 could regulate various metabolic processes to participate in the production of reactive oxygen species during oxidative stress [ 29 , 30 ]. SKP2 helps to inhibit oxidative stress induced-DNA damage and cell apoptosis, which limits the misincorporation of ROS-damaged dNTPs into genomic DNA, making cells more resistant to such stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…CYP1A2 was enriched in reactive oxygen species metabolic pathways. It has been reported that CYP1A2 could regulate various metabolic processes to participate in the production of reactive oxygen species during oxidative stress [ 29 , 30 ]. SKP2 helps to inhibit oxidative stress induced-DNA damage and cell apoptosis, which limits the misincorporation of ROS-damaged dNTPs into genomic DNA, making cells more resistant to such stress [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous works with mouse primary hepatocyte cultures [ 47 , 48 ] suggested that PKG was involved in phenobarbital-induced upregulation of CYP2b9/10 or CYP3A expression. A recent publication demonstrated that PKG can regulate the function of Nrf2 [ 49 ], a gene known to control the expression of P450s [ 50 ] and more specifically Cyp6a2 [ 51 ]. As Cyp6a2 expression has previously been shown to be controlled by phenobarbital [ 52 , 53 ], all these published data are consistent with our current data highlighting a direct link between PKG and the expression of the P450 Cyp6a2 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Nrf2 can also contribute to biodefense against increased reactive oxygen species by mediating the regulation of cytochrome P450 (CYP), a class of heme-containing monooxygenases. Nrf2 depletion has been shown to reduce liver microsomal cytochrome P450 content in the experiments of Takashi Ashino et al This is mainly due to increased expression of the P450 genes Cyp2a5 and Cyp2b10 by Nrf2 (Ashino et al 2020 ). Recent studies have shown that CYP may be involved in the development of lung injury, kidney injury, and liver injury in patients with COVID-19.…”
Section: Nrf2’s Antioxidant Roles In Covid-19mentioning
confidence: 99%